Britholite group minerals from REE-rich lithologies of Keivy Alkali Granite—Nepheline Syenite complex, Kola Peninsula, NW Russia - Zozulya, D.; Lyalina, L.; Macdonald, R.; Bagiński, B.; Savchenko, Y.; Jokubauskas, P. (Minerals, 2019)
The Keivy alkali granite-nepheline syenite complex, Kola Peninsula, NW Russia, contains numerous associated Zr-REE-Y-Nb occurrences and deposits, formed by a complex sequence of magmatic, late-magmatic, and post-magmatic (including pegmatitic, hydrothermal, and metasomatic) processes. The REE-rich lithologies have abundant (some of economic importance) and diverse britholite group minerals. The REE and actinides distribution in host rocks indicates that the emanating fluids were alkaline, with significant amounts of F and CO2. From chemical studies (REE and F variations) of the britholites the possible fluid compositions in different lithologies are proposed. Fluorbritholite-(Y) and britholite-(Y) from products of alkali granite (mineralized granite, pegmatite, quartzolite) formed under relatively high F activity in fluids with low CO2/H2O ratio. The highest F and moderate CO2 contents are characteristic of fluid from a mineralized nepheline syenite, resulting in crystallization of fluorbritholite-(Ce). Britholite group minerals (mainly fluorcalciobritholite and ‘calciobritholite’) from a nepheline syenite pegmatite formed from a fluid with composition changing from low F and high CO2 to moderate F and CO2. An extremely high F content is revealed for metasomatizing fluids emanating from alkali granitic magma and which affected the basic country rocks. The dominant substitution scheme for Keivy britholites is REE3+ + Si4+ = Ca2+ + P5+, showing the full range of ‘britholite’ and ‘calciobritholite’ compositions up to theoretical apatite.